Inhibition of renin-angiotensin system enzymes by leafy vegetables polyphenol extracts related to fertilizer micro-dosing and harvest time - Djibril Moussa, Modoukpè Imayath; Alashi, Adeola Monisola; Sossa-Vihotogbé, Carole Nadia Adjouavi; Akponikpè, Pierre B. Irénikatché; DJENONTIN, Jonas André; BACO, Mohamed Nasser; AKISSOE, H. NOËL; Aluko, Rotimi E (My University, 2019)
Increase in human population coupled with continuous rise in oxidatiye stress, related diseases requires arrailabitity oi rrearirricr f";.i;iik. ;.g;rbË; *ttiln polyphenol-rith §§urce§. Polypheuols are able to inhibit angioiensin-I convefting "r* süryme {ÀC§} and renin, theràby regulating blaod prÊssure Ëut this abilis can bô influenced by nutrient mânïrgem*nt during §lant grolnttr. Ëertilizer micrn-dôsing is a v*luahle nutrient management option, -wtrictr încreases rr{rp prerductiviqy *wittr minimal expenditure af resour(es. This study assessed the effecis ôf fertilizer micro- dssing and harvest times on inhibition nf AC§ and renin actirrities by aqueou§ ptllyphenol extracts from drnaranthus cruentus, Ocimum grotissirnum and §nlsnurn rr(rrocfltpon leaves, Different levels of urea (O, 20, 4O and 6O kg ha-1) with cow manur§ [5 t ha-r] or without manure (SO kg ha-t) TÂ/ers used to grow ttre leafy vegetalrles hefore they werê harvested three times at two {.â, cruentus} ànd four weeks intervals {û. grafissimum and §. mercrocûrpon}. Polyphenols were extracted from leaf powders using Brâter (1:2O ratio) and total phenolic cûntent [TPC], total flavonoids rrlntent (TFC), ACE and renin inhibition were assayed aecording to standard protocols. Ywo-way analysis of rrariance and Duncan's test (p<t).ûS) revealed that TFC {6$5.?Ot39.§1" to 1O24.83*1O2,S9 mg T1; gallic acid equivalent} and TFC {I"49.O2*?9.A2 t$ 276.L9*63.30 mg g-1; rutin equivalent} urere not affected by feriilizer doses and haryest fimes except TFC from O. gratfssimum,Inhibitions nf ÂCE {§.Z§àO.$tr" to 8.46*:0.42 mB rnL-r} and renin {-9§.41*2.?5 to 36.42+O.32Yo} activities by each specie !ÿere significantly affiected -by fertilizer dose and harvest timq. Production wittr cûw rnânure cambined with lsur or medium dnser of urea (3O or 4O kA tr*'r; followed by collection at the first two harvests are recommended for pôtypfrénol extracts Éitfr potential inhibition of renin-angiotensin system enz!runes.
Keywords: drn«rapt6us cruentus; Ocimum gratfssfmum; Saîanum müÇroÇûrpon; angiatensin-l converting enuyme; minetal f'ertilizer